Analisis Pesan Moral Dalam Film Jumbo Tahun 2025 - M.Gilang Gibran; Fifi Hasmawati; Sumaina Duku (Journal of Innovative and Creativity, 2026)
The development of the film industry in Indonesia over the past few decades has shown significant progress. The animated film Jumbo (2025) was chosen because its moral message is considered relevant to various audiences. This research aims to uncover and analyze the moral messages conveyed thru narrative and symbolic elements in the film. The method used is descriptive qualitative research with a semiotic approach by Charles Sanders Peirce, emphasizing the analysis of icons, indexes, and symbols. The research results show that the film Jumbo contains moral messages that encompass three main categories, namely the relationship between humans and God (spirituality and prayer), the relationship between humans with each other (empathy, friendship, self-acceptance, and anti-bullying), as well as the relationship between humans and the social environment (concern for other living beings). The film Jumbo not only serves as entertainment but also as an effective medium for preaching communication, instilling moral values thru the visual and symbolic language of animation.